Graphite piece containing TaC / Ta2C gradient coating and preparation method thereof
By designing the TaC/Ta2C gradient buffer layer on the surface of the graphite piece, the problem of low bond strength caused by the difference in thermal expansion coefficient between the TaC coating and the graphite substrate is solved, and the high bond strength and impact resistance are improved.
Patent Information
- Application Number
- CN202411703774.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The difference in thermal expansion coefficient between the TaC coating and the graphite substrate leads to low binding strength, prone to cracks, pores and thermal stress, and is prone to peeling during corrosive atmosphere and repeated rise and fall.
The TaC/Ta2C gradient buffer layer is designed to relieve thermal stress through the gradual transitional material properties and improve the bonding strength with the graphite substrate.
It effectively improves the bonding strength of TaC coating with graphite substrate, reduces the risk of cracks and peeling, extends the service life of the coating, and improves impact resistance.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductors, in particular to a graphite part containing a TaC / Ta2C gradient coating and a preparation method thereof. Background Art
[0002] Tantalum carbide (TaC) has the characteristics of high melting point, high hardness, high thermal conductivity and high chemical stability. The preparation of ultra-high temperature, corrosion-resistant and high-purity TaC coating on the surface of graphite material is expected to significantly extend the life of graphite components and inhibit the generation of crystal defects such as carbon inclusions, thereby improving the growth quality of semiconductor single crystals such as indium phosphide (InP), gallium arsenide (GaAs), silicon carbide (SiC), gallium nitride (GaN), gallium oxide (Ga2O3), aluminum nitride (AlN) or reducing process costs. The main difficulty that needs to be solved in TaC-coated graphite parts is that there is a large difference in physical properties such as thermal expansion coefficient between TaC coating and carbon material. The prepared coating has low bonding strength with the graphite substrate, and it is difficult to avoid cracks, pores and thermal stress. The coating is easy to peel off in actual corrosive atmosphere and repeated temperature rise and fall. The existing technology mainly avoids the problem of low bonding strength of the prepared coating caused by direct contact between TaC and carbon materials by alternately depositing silicon carbide composite layers, silicon carbide-tantalum carbide composite coatings, and tantalum carbide coatings multiple times. Therefore, it is very important to provide a TaC coating with high bonding strength on the surface of graphite parts.
[0003] TaC coated graphite parts have huge demand and broad application prospects in the market. At present, the mainstream manufacturing of TaC coated graphite parts relies on CVD TaC components. However, due to the high cost of CVD TaC production equipment and limited deposition efficiency, it has not yet completely replaced the traditional SiC coated graphite material. The sintering method can effectively reduce the cost of raw materials and can adapt to graphite parts with complex shapes, thereby meeting the needs of more different application scenarios. Depending on the sintering slurry, a buffer layer / TaC layer with gradually approaching thermal expansion coefficients can be prepared on the surface of graphite, thereby greatly improving the service life of the TaC coating, reducing production costs, and promoting the alternating renewal of advanced thermal field materials. However, TaC has low plasticity and poor thermal shock resistance, which makes the interface bonding strength with graphite low, and the configuration of the precursor slurry during the sintering process and the subsequent coating, sintering and other process conditions have a great influence on the quality of the final prepared graphite parts. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating. In the coating design, the ratio of TaC to Ta2C is set to form a buffer layer with gradient characteristics. The purpose of this layer is to alleviate the thermal stress caused by temperature changes through gradually transitioning material properties (such as thermal expansion coefficient, bonding strength, etc.). The TaC / Ta2C gradient buffer layer design effectively solves the bonding strength problem between the TaC coating and the graphite substrate, and reduces the cracks and peeling caused by the difference in thermal expansion coefficients, providing a more solid foundation for the application of TaC coated graphite parts, and has broad market prospects.
[0005] In one aspect, the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, which comprises at least the following steps:
[0006] Providing a slurry suspension 1 containing a tantalum source, a dispersant, and a binder, applying the slurry suspension 1 to the surface of a graphite part, and curing to form a first pre-coating layer;
[0007] Providing a slurry suspension 2 containing tantalum carbide, a sintering agent, a dispersant, and a binder, applying the slurry suspension 2 to the surface of the first pre-coating layer, drying to form a second pre-coating layer, and curing to obtain a preform, and sintering the preform to form a double-layer Ta2C buffer layer;
[0008] A suspension slurry 3 containing a tantalum source, a carbon source, a dispersant, and an adhesive is provided, the suspension slurry 3 is applied to the surface of the double-layer Ta2C buffer layer, solidified to form a third pre-coating layer, and the third pre-coating layer is sintered to form a TaC / Ta2C gradient coating.
[0009] As a preferred technical solution, the tantalum source in the slurry suspension 1 includes at least one of Ta2O5, Ta powder, TaOC interionic compound, and TaC powder, preferably Ta powder;
[0010] Preferably, the particle size of the Ta powder is 20nm-100nm, preferably 50nm-80nm, most preferably 60nm.
[0011] As an example, the particle size of the Ta powder may be 50 nm, 60 nm, 70 nm, or 80 nm.
[0012] Preferably, the purity of the Ta powder is ≥99wt%, preferably 99.99wt%.
[0013] As a preferred technical solution, the sintering agent includes at least one of Fe, Co, Ni, Cr, Al2O5, and acetylacetone, preferably nickel (Ni).
[0014] As a preferred technical solution, the purity of the tantalum carbide is 99.99wt%, the particle size is 100-2000nm, and the preferred particle size is 800-1200nm.
[0015] As an example, the particle size of the tantalum carbide may be 800 nm, 900 nm, 1000 nm, or 1200 nm.
[0016] As a preferred technical solution, the carbon source includes at least one of high-purity carbon powder, carbon black, glucose, graphene, acetylacetone, and TaC powder, preferably acetylacetone.
[0017] As a preferred technical solution, the tantalum source in the suspension slurry 3 is Ta2O5, Ta powder, TaC powder, TaCl 5、 At least one of tantalum standard solution and TaF5, preferably TaCl5.
[0018] As a preferred technical solution, the dispersant in the slurry suspension 1, the slurry suspension 2, and the suspension slurry 3 includes at least one of anhydrous ethanol, deionized water, ethylene glycol, methanol, and isopropanol, preferably anhydrous ethanol.
[0019] As a preferred technical solution, the binder in the slurry suspension 1, slurry suspension 2, and suspension slurry 3 includes at least one of polyvinyl butyral, polyvinyl alcohol, polyacrylamide, polyethylene oxide, phenolic resin, and graphite glue, preferably polyvinyl butyral.
[0020] Preferably, the weight average molecular weight (M W ) is 50000-120000, preferably 70000-90000.
[0021] As an example, the weight average molecular weight (M) of the polyvinyl butyral W ) can be 70000, 80000, 90000.
[0022] As a preferred technical solution, the added amount of tantalum source in the slurry suspension 1 is 0.5 g / mL-1.5 g / mL, preferably 0.7 g / mL-1 g / mL.
[0023] As an example, the added amount of tantalum source in the slurry suspension 1 can be 0.7 g / mL, 0.8 g / mL, 0.9 g / mL, or 1 g / mL.
[0024] As a preferred technical solution, the amount of binder added to the slurry suspension 1 is 2wt%-8wt%, preferably 3wt%-6wt%.
[0025] As an example, the amount of binder added to the slurry suspension 1 is 3wt%, 4wt%, 5wt%, or 6wt%.
[0026] As a preferred technical solution, the preparation method of the slurry suspension 1 includes: stirring and mixing a tantalum source with a dispersant and a binder, stirring and mixing until there are no particles, and then ultrasonically treating to obtain a slurry suspension, wherein: the amplitude of the variable amplitude is 20, the frequency is 15KHz-35KHz, the power is 800W-1200W, and the ultrasonic time is 20min-60min.
[0027] As a preferred technical solution, the mass ratio of the tantalum carbide and the sintering agent in the slurry suspension 2 is (20-50):(1-5), preferably (20-40):(1-3), and most preferably 30:1.
[0028] As an example, the mass ratio of the tantalum carbide to the sintering agent in the slurry suspension 2 may be 20:1, 30:1, 40:1, 20:3, 40:3, or 30:3.
[0029] As a preferred technical solution, the total mass ratio of the dispersant to the tantalum source and the sintering agent is (3-6):1, preferably 4:1.
[0030] As an example, the total mass ratio of the dispersant to the tantalum source and the sintering agent may be 3:1, 4:1, 5:1, or 6:1.
[0031] As a preferred technical solution, the amount of binder added to the slurry suspension 2 is 0.1wt%-3wt%, preferably 0.5wt%-1.5wt%, and most preferably 1wt%.
[0032] As an example, the amount of binder added to the slurry suspension 2 may be 0.5wt%, 1wt%, or 1.5wt%.
[0033] As a preferred technical solution, the preparation method of the slurry suspension 2 includes: mixing the tantalum carbide and the sintering agent, adding them to a ball mill for ball milling, the rotation speed is 500r / min-1000r / min, and the ball milling time is 5h-10h; then stirring and mixing with a dispersant and a binder, stirring and mixing until there are no particles, and then ultrasonically treating to obtain a slurry suspension, during the ultrasonic treatment: the amplitude of the variable amplitude is 20, the frequency is 15KHz-35KHz, the power is 800W-1200W, and the ultrasonic time is 20min-60min.
[0034] As a preferred technical solution, the Ta in the slurry suspension 3 5+ The ion concentration is 0.1-0.5 mol / L, preferably 0.4 mol / L.
[0035] As an example, the slurry suspension 3 contains Ta 5+ The ion concentration is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, and 0.4mol / L.
[0036] As a preferred technical solution, the molar ratio of the tantalum source to the carbon source in the slurry suspension 3 is (0.8-1.2):1, preferably 1:1.
[0037] As an example, the molar ratio of the tantalum source to the carbon source in the slurry suspension 3 may be 0.8:1, 0.9:1, 1:1, 1.1:1, or 1.2:1.
[0038] As a preferred technical solution, the amount of binder added to the slurry suspension 3 is 0.1wt%-0.8wt%, preferably 0.2wt%-0.6wt%, and most preferably 0.4wt%.
[0039] As an example, the amount of binder added to the slurry suspension 3 may be 0.2wt%, 0.3wt%, 0.3wt%, 0.5wt%, or 0.6wt%.
[0040] As a preferred technical solution, the ratio of the total mass of the dispersant to the tantalum source and the carbon source in the slurry suspension 3 is (15-20):(2-5), preferably 17:3.
[0041] As a preferred technical solution, the slurry suspension 3 is synthesized by a solvothermal method, the solvothermal reaction temperature is 180° C.-220° C., and the solvothermal reaction time is 8 h-16 h.
[0042] As a preferred technical solution, the preparation method of the preform is as follows: applying the slurry suspension 1 to the surface of the graphite part, placing it in a vacuum drying oven after natural drying, and keeping it warm at 150-250°C for 8h-16h to form a first precoating layer and solidify it; then applying the slurry suspension 2 to the surface of the first precoating layer, placing it in a vacuum drying oven after natural drying, and keeping it warm at 150-250°C for 8h-16h to form a second precoating layer and solidify it to obtain a preform.
[0043] As a preferred technical solution, the thickness of the first pre-coating layer is ≤50 μm, preferably 20 μm-30 μm.
[0044] As a preferred technical solution, the thickness of the second pre-coating layer is ≤80 μm, preferably 40 μm-60 μm.
[0045] As a preferred technical solution, the graphite piece is obtained by the following method: polishing the graphite block to be smooth, performing ultrasonic cleaning, and sintering the graphite block at ≥2300°C for ≥3h to obtain the graphite piece.
[0046] Preferably, the graphite piece is obtained by the following method: high-purity graphite is cut to obtain a graphite block, the surface of the graphite block is polished smooth using 100 mesh, 220 mesh, 400 mesh, and 800 mesh sandpaper in sequence, and the graphite block is placed in alcohol for ultrasonic cleaning. After cleaning, the graphite block is placed in a graphite induction furnace, and sintered at ≥2300°C for at least 3 hours in an argon atmosphere (slightly positive pressure) to obtain a graphite piece.
[0047] The present invention increases the graphitization degree of graphite, improves the purity of graphite and increases the porosity of graphite through the above treatment.
[0048] As a preferred technical solution, the coating method includes one of vacuum infiltration, spraying (ultrasonic spraying), flow coating, and brushing, preferably spraying.
[0049] TaC coated graphite parts include: crucibles, seed crystal holders, and guide rings in the PVT method for growing SiC and AlN single crystal furnaces; heaters in MOCVDGaN epitaxial layer growth; wafer carriers, baffles, external floating air nozzles, air guides, pneumatic ducts, etc. in SiC epitaxy. Since the above graphite parts have different shapes and sizes, the coating process matches the corresponding vacuum infiltration, spraying (ultrasonic spraying), curtain coating, and brushing for slurry suspension coating.
[0050] As a preferred technical solution, the preform sintering is specifically as follows: placing the preform in a sintering furnace, keeping the temperature at 1600° C.-1800° C. and a vacuum environment of 0.1 Pa-10 Pa for 10 min-30 min.
[0051] As a preferred technical solution, the double-layer Ta2C buffer layer includes a large-grained dense Ta2C bottom layer and a small-grained porous Ta2C surface layer.
[0052] Preferably, the thickness of the large-grained dense Ta2C bottom layer is ≤10 μm, preferably 5 μm-10 μm.
[0053] Preferably, the thickness of the small-grain porous Ta2C surface layer is ≤20 μm, preferably 15 μm-20 μm.
[0054] As a preferred technical solution, the thickness of the third pre-coating layer is 80 μm-150 μm, preferably 100 μm-150 μm.
[0055] As a preferred technical solution, the preparation method of the TaC / Ta2C gradient coating is specifically as follows: applying the suspension slurry 3 to the surface of the double-layer Ta2C buffer layer, placing it in a vacuum drying oven after natural drying, keeping it at 150-250°C for 8h-16h to form a third pre-coating layer and solidifying it, and performing high-temperature sintering on the third pre-coating layer, the high-temperature sintering temperature is 2100°C-2300°C, the time is 0.5h-1h, the vacuum atmosphere is 0.1Pa-10Pa, and the TaC / Ta2C gradient coating is formed after natural cooling.
[0056] In order to ensure the service life of the TaC coating under various corrosion conditions, the present invention effectively solves the difference in thermal expansion coefficient between the TaC coating and graphite by preparing a double-layer Ta2C buffer layer. Specifically, the double-layer Ta2C buffer layer provided by the present invention includes a large-grained dense Ta2C bottom layer with a thickness of 5μm-10μm and a small-grained porous Ta2C surface layer with a thickness of 15μm-20μm. Compared with the traditional buffer layer (a single dense metal layer and an overly loose porous carbide layer), it has a high bonding force with the graphite substrate, and can alleviate the thermal stress generated by the expansion of TaC crystals, effectively improve the plasticity of the coating interface, and improve the impact resistance.
[0057] Specifically, the present invention optimizes the formula of slurry suspension 1, slurry suspension 2, and suspension slurry 3 in which the three elements Ta, O, and C are dispersed and evenly distributed, so as to ensure that after sintering, a large-grained dense Ta2C bottom layer with high bonding strength to the graphite substrate is obtained; a loose and porous small-grained porous Ta2C surface layer; and a dense, crack-free and hole-free TaC bottom layer. In particular, the sintering agent in slurry suspension 2 is controlled to be metallic nickel, and the mass ratio of tantalum carbide and metallic nickel is controlled to be 30:1, so as to ensure the subsequent formation of a loose and porous small-grained porous Ta2C surface layer. The thickness of the first pre-coating layer, the second pre-coating layer, and the thickness of the third pre-coating layer are further coordinated and controlled to avoid coating cracking and coating peeling problems.
[0058] Furthermore, the present invention forms a TaC coating of a certain thickness on the surface of the double-layer Ta2C buffer layer by optimizing the formula of the suspension slurry 3 in which the three elements Ta, O, and C are dispersed and evenly distributed and the subsequent sintering process. The TaC coating, as the outermost layer, has the largest crystal size, no obvious holes and cracks, and exhibits free oriented growth, which can most effectively resist the corrosive atmosphere and adapt to repeated heating and cooling processes.
[0059] On the other hand, the present invention provides a TaC / Ta2C gradient coating, which comprises, from top to bottom: a TaC layer, a small-grain porous Ta2C surface layer, and a large-grain dense Ta2C bottom layer.
[0060] The TaC / Ta2C gradient coating provided by the present invention has free orientation, no surface cracks, and high density, and an optimized, high-quality gradient coating graphite part is prepared to better meet practical application requirements.
[0061] Beneficial Effects
[0062] 1. The present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating. Through the design of the TaC / Ta2C gradient buffer layer, a high bonding force between the coating and graphite is ensured, and the difference in thermal expansion coefficients between graphite and TaC is reduced.
[0063] 2. The double-layer Ta2C buffer layer provided by the present invention includes a large-grained dense Ta2C bottom layer with a thickness of 5μm-10μm and a small-grained porous Ta2C surface layer with a thickness of 15μm-20μm. Compared with the traditional buffer layer (a single dense metal layer and an overly loose porous carbide layer), it has a high bonding strength with the graphite substrate, can alleviate the thermal stress caused by the expansion of TaC crystals, effectively improve the plasticity of the coating interface, and enhance the impact resistance.
[0064] 3. The present invention optimizes the formulas of slurry suspension 1, slurry suspension 2 and suspension slurry 3 in which the three elements Ta, O and C are dispersed and evenly distributed, thereby ensuring that after sintering, a large-grained dense Ta2C bottom layer with high bonding strength to the graphite substrate; a loose and porous small-grained porous Ta2C surface layer; and a dense TaC bottom layer without cracks and holes are obtained.
[0065] 4. The present invention controls the sintering agent in the slurry suspension 2 to be metallic nickel, and controls the mass ratio of tantalum carbide to metallic nickel to be 30:1, thereby ensuring the subsequent formation of a small-grained porous Ta2C surface layer with a loose porous structure. The thickness of the first pre-coating layer, the second pre-coating layer, and the thickness of the third pre-coating layer are further controlled to avoid coating cracking and coating peeling problems.
[0066] 5. The present invention forms a TaC coating of a certain thickness on the surface of the double-layer Ta2C buffer layer by optimizing the formula of the suspension slurry 3 in which the three elements Ta, O, and C are dispersed and evenly distributed and the subsequent sintering process. The TaC coating, as the outermost layer, has the largest crystal size, no obvious holes and cracks, and exhibits free oriented growth, which can most effectively resist the corrosive atmosphere and adapt to repeated heating and cooling processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is a schematic diagram of the TaC / Ta2C gradient coating structure obtained in Example 1, wherein 1: TaC layer, 2: small-grained porous Ta2C surface layer, 3: large-grained dense Ta2C bottom layer.
[0068] Figure 2This is the SEM characterization image of the TaC / Ta2C gradient coating obtained in Example 1, in which the left side is a cross-sectional image (magnification ×500) and the right side is a surface image (magnification ×3000).
[0069] Figure 3 These are the XRD characterization graphs of the TaC layer, small-grain porous Ta2C surface layer, and large-grain dense Ta2C bottom layer in Example 1. The left side of the figure shows the XRD characterization graphs of the small-grain porous Ta2C surface layer (1) and the large-grain dense Ta2C bottom layer (2), and the right side shows the XRD characterization graph of the TaC layer, where 1 is Ta2C and 2 is TaC.
[0070] Figure 4 This is the SEM image of the double-layer Ta2C buffer layer in comparison 1 (magnification ×30).
[0071] Figure 5 This is the SEM image of the single-layer Ta2C buffer layer in Comparative Examples 2 and 3 (without loose porous structure). The left side of the image corresponds to Comparative Example 2 (magnification ×897), and the right side corresponds to Comparative Example 3 (magnification ×1000).
[0072] Figure 6 This is the SEM characterization image of the tantalum-tantalum carbide composite coating prepared in Comparative Example 4 (magnification ×800).
[0073] Figure 7 This is a SEM characterization image of a single-layer Ta2C layer provided for comparative example 5, with the left side of the image magnified by ×500 and the right side by ×50.
[0074] Figure 8 This is a SEM characterization image of a single-layer Ta2C layer provided for comparative example 6, with the left side of the image magnified by ×5000 and the right side magnified by ×1000.
[0075] Fig. 9 This is the SEM characterization image of the single-layer Ta2C layer provided for Comparative Example 7, magnified at ×700. DETAILED DESCRIPTION
[0076] The present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, wherein the Ta2C gradient layer is used as a buffer layer, and the thickness thereof is 5μm-10μm and 15μm-20μm, respectively. The first layer of Ta2C coating is tightly bonded to the graphite substrate, and each grain size is large and tightly bonded, while the second layer of Ta2C layer has smaller grains and a loose porous structure as a whole, which can alleviate the thermal stress generated by the expansion of TaC crystals. The double-layer Ta2C coating is different from the traditional buffer layer (i.e., a single dense metal layer and an overly loose porous carbide layer). This double-layer buffer layer combines the advantages of both. The Ta2C layers of two crystal sizes and thicknesses not only ensure the high bonding force between the coating and graphite, but also make the thermal expansion coefficients between the graphite and the TaC coating close layer by layer. This design can effectively alleviate the thermal stress generated by the expansion of TaC crystals under high temperature conditions and reduce the risk of cracking and peeling of the coating. The TaC crystals in the outermost layer are the largest, with no obvious holes or cracks, and grow in a freely oriented manner. They can most effectively resist corrosive atmospheres and adapt to repeated temperature rise and fall processes, thus improving the overall performance and service life of graphite parts.
[0077] Example 1
[0078] Embodiment 1 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, comprising the following steps:
[0079] Providing a slurry suspension 1 containing a tantalum source, a dispersant, and a binder, applying the slurry suspension 1 to the surface of a graphite part, and curing to form a first pre-coating layer;
[0080] Providing a slurry suspension 2 containing tantalum carbide, a sintering agent, a dispersant, and a binder, applying the slurry suspension 2 to the surface of the first pre-coating layer, drying to form a second pre-coating layer, and curing to obtain a preform, and sintering the preform to form a double-layer Ta2C buffer layer;
[0081] Provide a suspension slurry 3 (Ta 3.9 O 7.3 C), applying the suspension slurry 3 to the surface of the double-layer Ta2C buffer layer, solidifying to form a third pre-coating layer, and sintering the third pre-coating layer to form a TaC / Ta2C gradient coating.
[0082] The tantalum source in the slurry suspension 1 is Ta powder, the particle size of the Ta powder is 60nm, and the purity of the Ta powder is 99.99wt%, Beijing Zhongke Yannuo New Material Technology Co., Ltd.
[0083] The sintering agent is nickel (Ni), produced by Jiangxi Guocai Technology Co., Ltd., with a purity of 99.99wt% and a particle size of 1000nm.
[0084] The purity of the tantalum carbide is 99.99wt%, and the particle size is 1000nm, Beijing Yanbang New Material Technology Co., Ltd.
[0085] The carbon source is acetylacetone.
[0086] The tantalum source in the suspension slurry 3 is TaCl5.
[0087] The dispersants in the slurry suspension 1, slurry suspension 2 and suspension slurry 3 are all anhydrous ethanol.
[0088] The binders in the slurry suspension 1, slurry suspension 2 and suspension slurry 3 are all polyvinyl butyral.
[0089] The weight average molecular weight (M W ) is 70000-90000, Shanghai McLean Biochemical Technology Co., Ltd.
[0090] The added amount of tantalum source in the slurry suspension 1 is 0.83 g / mL.
[0091] The amount of binder added to the slurry suspension 1 is 5 wt %.
[0092] The preparation method of the slurry suspension 1 includes: stirring and mixing a tantalum source with a dispersant and a binder, stirring and mixing until there are no particles, and then putting the mixture into an ultrasonic cell crusher for ultrasonic treatment to obtain a slurry suspension. During the ultrasonic treatment, the amplitude of the variable amplitude is 20, the frequency is 19.5KHz, the power is 950W, and the ultrasonic time is 20min.
[0093] The mass ratio of the tantalum carbide to the sintering agent in the slurry suspension 2 is 30:1.
[0094] The total mass ratio of the dispersant to the tantalum source and the sintering agent is 4:1.
[0095] The amount of binder added to the slurry suspension 2 is 1 wt %.
[0096] The preparation method of the slurry suspension 2 includes: mixing the tantalum carbide and the sintering agent, adding them into a ball mill for ball milling, the rotation speed is 600r / min, and the ball milling time is 8h; then stirring and mixing with a dispersant and a binder, stirring and mixing until there are no particles, and then putting them into an ultrasonic cell crusher for ultrasonic treatment to obtain a slurry suspension, during the ultrasonic treatment: the amplitude of the variable pole is 20, the frequency is 19.5KHz, the power is 950W, and the ultrasonic time is 20min.
[0097] The slurry suspension 3 contains Ta 5+ The ion concentration is 0.4 mol / L.
[0098] The molar ratio of the tantalum source to the carbon source in the slurry suspension 3 is 1:1.
[0099] The amount of binder added to the slurry suspension 3 is 0.4 wt %.
[0100] The mass ratio of the dispersant to the total mass of the tantalum source and the carbon source in the slurry suspension 3 is 17:3.
[0101] The slurry suspension 3 is synthesized by a solvothermal method, the solvothermal reaction temperature is 200° C., and the solvothermal reaction time is 12 h.
[0102] The preparation method of the preform is as follows: the slurry suspension 1 is applied to the surface of the graphite part, and after being naturally dried, it is placed in a vacuum drying oven, and kept warm at 200°C for 10 hours to form a first pre-coating layer and solidify; then the slurry suspension 2 is applied to the surface of the first pre-coating layer, and after being naturally dried, it is placed in a vacuum drying oven, and kept warm at 200°C for 10 hours to form a second pre-coating layer and solidify to obtain the preform.
[0103] The thickness of the first pre-coating layer is 25 μm.
[0104] The thickness of the second pre-coating layer is 50 μm.
[0105] The graphite piece is obtained in the following manner: high-purity graphite is cut to obtain a graphite block (10cm*10cm*0.5cm), the surface of the graphite block is polished smooth using 100 mesh, 220 mesh, 400 mesh, and 800 mesh sandpaper in sequence, and the graphite block is placed in alcohol for ultrasonic cleaning. After cleaning, the graphite block is placed in a graphite induction furnace, sintered at 2600° C. for 3 hours, and the sintering atmosphere is argon (slightly positive pressure), so as to obtain the graphite piece.
[0106] The coating method is spraying.
[0107] The preform sintering is specifically as follows: placing the preform in a sintering furnace, and keeping the temperature at 1800° C. and 3 Pa in a vacuum environment for 30 minutes.
[0108] The double-layer Ta2C buffer layer comprises a large-grained dense Ta2C bottom layer and a small-grained porous Ta2C surface layer.
[0109] The thickness of the large-grained dense Ta2C bottom layer is 10 μm.
[0110] The thickness of the small-grain porous Ta2C surface layer is 20 μm.
[0111] The thickness of the third pre-coating layer is 120 μm.
[0112] The preparation method of the TaC / Ta2C gradient coating is specifically as follows: applying the suspension slurry 3 to the surface of the double-layer Ta2C buffer layer, placing it in a vacuum drying oven after natural drying, keeping it at 200°C for 10 hours to form a third pre-coating layer and solidifying it, and performing high-temperature sintering on the third pre-coating layer at a temperature of 2300°C, a time of 0.5 hours, a vacuum atmosphere of 5Pa, and forming a TaC / Ta2C gradient coating after natural cooling.
[0113] See also Figure 1-3 On the other hand, Example 1 of the present invention provides a TaC / Ta2C gradient coating, which includes, from top to bottom: a TaC layer 1, a small-grained porous Ta2C surface layer 2, and a large-grained dense Ta2C bottom layer 3.
[0114] Comparative Example 1
[0115] Comparative Example 1 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating. The specific implementation method is the same as that of Example 1, except that the thickness of the first pre-coating layer is 150 μm and the thickness of the second pre-coating layer is 750 μm. This thicker pre-coating layer design leads to stress mismatch between the coatings, thereby affecting the overall bonding performance. The SEM image of the formed double-layer Ta2C buffer layer is shown in FIG. Figure 4 , multiple cracks were observed. These cracks were mainly caused by the fact that the pre-coating with too much thickness failed to effectively relieve thermal stress during the coating and sintering process, which affected the integrity of the coating and therefore no subsequent preparation was performed. It can be seen that it is extremely necessary to reasonably set the thickness of the pre-coating to prevent cracking and improve the bonding strength.
[0116] Comparative Example 2
[0117] Comparative Example 2 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, and its specific implementation method is the same as that of Example 1, except that the mass ratio of tantalum carbide to sintering agent in the slurry suspension 2 is 30:2, and the SEM image of the formed single-layer Ta2C buffer layer is shown in FIG. Figure 5 , this change in ratio results in the formation of a single-layer Ta2C buffer layer lacking the required loose porous structure, and the coating is tightly crystallized and does not undergo subsequent preparation. The lack of such a structure may affect the thermal stress relief ability of the coating, leading to damage or peeling of the coating in practical applications.
[0118] Comparative Example 3
[0119] Comparative Example 3 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, and its specific implementation method is the same as that of Example 1, except that the mass ratio of tantalum carbide to sintering agent in the slurry suspension 2 is 30:3, and the SEM image of the formed single-layer Ta2C buffer layer is shown in FIG. Figure 5 , it was observed that the coating crystallized tightly and did not form the expected loose porous structure. Although the dense coating can provide a certain bonding strength, the lack of a loose porous structure means that the coating may not be able to effectively relieve the stress concentration caused by expansion when facing high temperature and thermal stress. A single dense Ta2C layer may increase the brittleness of the coating, ultimately affecting the service life and performance stability of the coating.
[0120] Comparative Example 4
[0121] Comparative Example 4 of the present invention is a tantalum-tantalum carbide composite coating prepared according to the scheme of Example 1 in the preparation method of a tantalum-tantalum carbide composite coating and its products in patent CN 115637419 A. In terms of the buffer layer components, the thermal expansion coefficients of Ta and Ta2C are similar, and both can play a role in relieving thermal stress. However, the melting point of tantalum metal is much lower than that of Ta2C, and it is easy to soften at a high temperature of 2600°C. Such a thin buffer layer is very likely to warp and bend during the rapid heating and cooling process, resulting in a sharp increase in coating stress and cracking of the coating. In addition, in terms of the morphology of the buffer layer, the SEM image of the tantalum-tantalum carbide composite coating can be seen in FIG. Figure 6 , it can be seen that: the tantalum layer is very tightly bonded, but the thermal expansion coefficient of tantalum is still different from that of graphite, and its buffering effect is worse than that of the porous tantalum layer or Ta2C layer. Therefore, even if the tantalum layer has a strong bond in the microstructure, it cannot effectively cope with the thermal stress under high temperature conditions. Its buffering effect is not as good as the porous tantalum layer or Ta2C layer.
[0122] Comparative Example 5
[0123] Comparative Example 5 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, and its specific implementation method is the same as that of Example 1, except that the tantalum source and carbon source in the slurry suspension 2 are replaced with TaCl5 and carbon powder, and only a single layer of Ta2C is prepared. The coating has many cracks and holes and is uneven, and has a low density. It cannot completely cover the graphite substrate, and thus cannot be used as a good buffer intermediate layer. In the preparation process of tantalum carbide coating, it is crucial to select a suitable precursor to ensure that the coating's performance meets the actual application requirements.
[0124] Comparative Example 6
[0125] Comparative Example 6 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, and its specific implementation is the same as that of Example 1, except that the tantalum source and carbon source in the slurry suspension 2 are replaced with Ta2O5 and carbon powder, and only a single layer of Ta2C is prepared. The number of cracks and holes in the coating is appropriately reduced compared to Comparative Example 5, and the TaC grains begin to connect and crystallize. This change helps to improve the stability and structural integrity of the coating. However, since the distribution of pores is still uneven, this leads to insufficient buffering of the coating, and it is impossible to effectively reduce the stress caused by the difference in thermal expansion coefficients between materials.
[0126] Comparative Example 7
[0127] Comparative Example 7 of the present invention provides a method for preparing a graphite part containing a TaC / Ta2C gradient coating, and its specific implementation method is the same as that of Example 1, except that the dispersant anhydrous ethanol in the slurry suspension 2 is replaced by deionized water, and only a single-layer Ta2C layer is prepared. In the process of using deionized water as a dispersant, the uniform dispersion of the solid powder is significantly reduced. Due to the high surface tension of deionized water, it is difficult for solid particles to be fully dispersed in its medium, resulting in agglomeration of the powder. This agglomeration not only affects the fluidity and formability of the slurry, but also introduces uneven TaC grain size into the porous Ta2C layer finally prepared. This unevenness directly affects the physical and mechanical properties of the coating, making it unable to meet the requirements as a good buffer intermediate layer.
[0128] Performance Testing
[0129] This experiment aims to evaluate the effect of different coating structures on the corrosion resistance of graphite parts, especially the performance under extreme conditions. According to the preparation process in Example 1 (graphite parts containing TaC / Ta2C gradient coating), Comparative Example 3 (graphite parts containing only dense TaC coating), Comparative Example 6 (graphite parts containing only loose TaC coating), and Comparative Example 7 (graphite parts containing only loose TaC coating), we prepared the corresponding coating on a graphite disk with a diameter of 100 mm. As shown in the figure, it is placed in a graphite crucible containing 50% volume of SiC powder to simulate the SiC crystal growth atmosphere of 2600°C. This high temperature environment can effectively simulate the corrosion conditions that may be encountered in actual applications, ensuring the authenticity and effectiveness of the test. We evaluated the corrosion resistance of TaC-coated graphite parts prepared in four cases, in which one corrosion test lasted for 6 hours and the atmosphere was Ar gas (102-103kpa). When a graphite substrate was exposed and corroded, it was considered to be a failure, and the number of corrosion points was recorded. Comparative Examples 6 and 7 failed to maintain the integrity of the coating in a corrosion experiment and can be regarded as failure cases. The reasons for these failures are mainly attributed to the fact that their coating structures are not dense, resulting in a lack of sufficient protection in a corrosive atmosphere. The TaC coatings prepared in Examples 1 and 4 can have a certain service life under corrosion conditions. In particular, Example 1, due to its use of a gradient coating design, has better thermal shock resistance, which makes its corrosion resistance under extreme conditions significantly better than that of a graphite part containing only a dense TaC coating (Comparative Example 4). The superiority of this structure is that the gradient layer can effectively alleviate thermal stress and reduce the risk of coating cracking caused by temperature changes, thereby extending the service life of the coating. The results are shown in Table 1.
[0130] Table 1
[0131]
Claims
1. A method for preparing a graphite part containing a TaC / Ta2C gradient coating, characterized in that: At least the following steps are included: Providing a slurry suspension 1 containing a tantalum source, a dispersant, and a binder, applying the slurry suspension 1 to the surface of a graphite part, and curing to form a first pre-coating layer; Providing a slurry suspension 2 containing tantalum carbide, a sintering agent, a dispersant, and a binder, applying the slurry suspension 2 to the surface of the first pre-coating layer, drying to form a second pre-coating layer, and curing to obtain a preform, and sintering the preform to form a double-layer Ta2C buffer layer; A suspension slurry 3 containing a tantalum source, a carbon source, a dispersant, and an adhesive is provided, the suspension slurry 3 is applied to the surface of the double-layer Ta2C buffer layer, solidified to form a third pre-coating layer, and the third pre-coating layer is sintered to form a TaC / Ta2C gradient coating.
2. According to the method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 1, the sintering agent comprises at least one of Fe, Co, Ni, Cr, Al2O5, and acetylacetone.
3. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 1, characterized in that: The mass ratio of the tantalum carbide to the sintering agent in the slurry suspension 2 is (20-50): (1-5).
4. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 1, characterized in that: The graphite piece is obtained by the following method: grinding a graphite block smooth, performing ultrasonic cleaning, and sintering the graphite block at a temperature of ≥2300°C for ≥3h to obtain the graphite piece.
5. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 4, characterized in that: The thickness of the first pre-coating layer is ≤50 μm, and the thickness of the second pre-coating layer is ≤80 μm.
6. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 5, characterized in that: The double-layer Ta2C buffer layer comprises a large-grained dense Ta2C bottom layer and a small-grained porous Ta2C surface layer.
7. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 6, characterized in that: The thickness of the large-grain dense Ta2C bottom layer is ≤10 μm.
8. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 7, characterized in that: The thickness of the small-grain porous Ta2C surface layer is ≤20 μm, preferably 15 μm-20 μm.
9. The method for preparing a graphite part containing a TaC / Ta2C gradient coating according to claim 8, characterized in that: The thickness of the third pre-coating layer is 80 μm-150 μm.
10. A TaC / Ta2C gradient coating prepared by the method for preparing a graphite part containing a TaC / Ta2C gradient coating according to any one of claims 1 to 9, characterized in that: From top to bottom, it includes: TaC layer, small-grained porous Ta2C surface layer, and large-grained dense Ta2C bottom layer.
Citation Information
Patent Citations
Tantalum carbide-coated carbon material and manufacturing method for same
CN103922797A
Low-cost tantalum carbide coating preparation method
CN106699228A
Composite coating for improving surface performance of carbon-based electrode, graphite electrode and preparation method
CN115404452A
Preparation method of double-layer tantalum carbide coating and graphite component
CN117964403A
Tantalum carbide composite coating as well as preparation method and application thereof
CN118851797A
Cited By
Tantalum carbide coating, preparation method thereof and tantalum carbide product
CN120229970A